Nitric Oxide Stress Induces Different Responses but Mediates Comparable Protein Thiol Protection in Bacillus subtilis and Staphylococcus aureus - Hochgräfe, Falko (American Society for Microbiology (ASM), 2008)
The nonpathogenic Bacillus subtilis and the pathogen Staphylococcus aureus are gram-positive model organisms that have to cope with the radical nitric oxide (NO) generated by nitrite reductases of denitrifying bacteria and by the inducible NO synthases of immune cells of the host, respectively. The response of both microorganisms to NO was analyzed by using a two-dimensional gel approach. Metabolic labeling of the proteins revealed major changes in the synthesis pattern of cytosolic proteins after the addition of the NO donor MAHMA NONOate. Whereas B. subtilis induced several oxidative stress-responsive regulons controlled by Fur, PerR, OhrR, and Spx, as well as the general stress response controlled by the alternative sigma factor SigB, the more resistant S. aureus showed an increased synthesis rate of proteins involved in anaerobic metabolism. These data were confirmed by nuclear magnetic resonance analyses indicating that NO causes a drastically higher increase in the formation of lactate and butanediol in S. aureus than in B. subtilis. Monitoring the intracellular protein thiol state, we observed no increase in reversible or irreversible protein thiol modifications after NO stress in either organism. Obviously, NO itself does not cause general protein thiol oxidations. In contrast, exposure of cells to NO prior to peroxide stress diminished the irreversible thiol oxidation caused by hydrogen peroxide.